Functional Analysis of Short Linear Motifs in the Plant Cyclin-Dependent Kinase Inhibitor SIAMESE - Kumar, Narender (Plant Physiol, 2018)
Endoreplication, a modified cell cycle in which DNA is replicated without subsequent cell division, plays an important but poorly understood role in plant growth and in plant responses to biotic and abiotic stress. The Arabidopsis (Arabidopsis thaliana) SIAMESE (SIM) gene encodes the first identified member of the SIAMESE-RELATED (SMR) family of cyclin-dependent kinase inhibitors. SIM controls endoreplication during trichome development, and sim mutant trichomes divide several times instead of endoreplicating their DNA. The SMR family is defined by several short linear amino acid sequence motifs of largely unknown function, and family members have little sequence similarity to any known protein functional domains. Here, we investigated the roles of the conserved motifs in SIM site-directed Arabidopsis mutants using several functional assays. We identified a potential cyclin-dependent kinase (CDK)-binding site, which bears no resemblance to other known CDK interaction motifs. We also identified a potential site of phosphorylation and two redundant nuclear localization sequences. Surprisingly, the only motif with similarity to the other family of plant CDK inhibitors, the INHIBITOR/INTERACTOR OF CDC2 KINASE/KIP-RELATED PROTEIN proteins, is not required for SIM function in vivo. Because even highly divergent members of the SMR family are able to replace SIM function in Arabidopsis trichomes, it is likely that the results obtained here for SIM will apply to other members of this plant-specific family of CDK inhibitors.